An integrated separation technology for high fluoride-containing wastewater treatment: Fluoride removal, membrane fouling behavior and control - Qiu, Yangbo; Ren, Long-Fei; Shao, Jiahui; Xia, Lei; Zhao, Yan (Journal of cleaner production, 2022)
The high concentration of fluoride in aqueous, which exacerbated by the discharged wastewater from semiconductor, electroplating, metallurgical and ceramics industries, has gone far beyond the World Health Organization (WHO) standard and seriously affected the health of human life. This study aims to validate the deep removal of fluoride from high fluoride-containing wastewater by using an integrated precipitation/crystallization/ultrafiltration (UF)/reverse osmosis (RO) system. The system enables an extremely low residual fluoride concentration (down to 0.25 mg L−1) qualified WHO standard, which was much lower than those of other reported membrane-based processes. In particular, the application of crystallization rather than conventional coagulation/flocculation was demonstrated to be effective in reducing fluoride, turbidity and sludge water content. Membrane fouling analysis indicated that UF membrane scaling was attributed to the CaF2 particles deposition at recovery rates of 70%–90%. RO membrane fouling behaviors were identified at recovery rate of 50% (organic fouling), 70% (inorganic scaling occurred and organic fouling) and 80% (inorganic scaling and organic fouling). Meanwhile, UF/RO membrane scaling/fouling could be removed by pure water cleaning (UF) and Na2CO3/NaOH/HCl cleaning (RO). Results of this work shall provide useful information on the application of a precipitation/crystallization/UF/RO system to purify and recover high fluoride-containing wastewater. [Display omitted] ●A new integrated system for fluoride-containing wastewater treatment was developed.●Crystallization process reduced fluoride, turbidity and sludge water content.●UF/RO fouling behaviors were identified along the permeate recovery rates.●Residual fluoride in integrated system effluent qualified WHO standard.